Mama Shamsi at the bazaar [book with audioplayer] - Hassani, Mojdeh; Iravani, Samira ([Library Ideas, LLC], 2023)
Samira is excited to go to the bazaar with her grandmother for the first time, but finds the bustling market to be intimidating, until Mama Shamsi helps her find a way to feel safe.